Analysis of genetics variation of the ndhF gene sequence in Antrophyum sp. NCBI popset 2496377569 using in silico RFLP - Hafizah Fadhilah; Afifatul Achyar (Tropical Genetics, 2023)
Antrophyum is one type of the largest and most diverse of the vittarioid ferns (Pteridaceae) in tropical Asia and the Pacific Islands. The data found in the Antrophyum study is still relatively sparse because the diversity of the genus is still uncertain. ndhF gene is an inherited gene from chloroplast DNA (NADH dehydrogenase five). Chloroplast DNA controls the production of ribosomal RNA (rRNA), transfer RNA (tRNA), and most of the proteins contained in the organelles chloroplast. Genes are commonly used in molecular studies such as the analysis of genetic variation in plants.. Genetic variation indicates that the greater the genetic variation that occurs in a population, the better its ability to adapt to the environment.. Besides that, determining genetic variation can also prevent extinction of a plant. This study aims to analyze genetic variation in the ndhF gene sequence of Antrophyum sp. NCBI PopSet 2496377569. In this study, the RFLP molecular marker was used which was carried out in silico using two restriction enzymes, PciI and ScaI.. The results of this study showed that there was no genetic variation in digestion with the restriction enzyme PciI, whereas in ScaI there was genetic variation with 3 allele variations from 23 PopSet sequences 2496377569 in NCBI.